Big Data Privacy in Biomedical Research (International Journal of Innovative Research in Computer Science & Technology, 2022)
The examination of patient data, which  may contain personally identifiable information, is a  common part of biomedical research. If these data are  misused, it could result in the disclosure of private patient  information, which would put the patients' right to privacy  at risk. The challenge of protecting the privacy of patients  in an era dominated by big data has garnered a growing  amount of attention in recent years. There have been a lot  of different privacy approaches created to protect against  different attack models. In the context of research in  biomedicine, this publication provides a review of  pertinent subjects. It is discussed how technology can  protect privacy, particularly in relation to record linking,  synthetic data production, and the privacy of genomic data.  In addition to this, we conduct an analysis of the ethical  implications of the privacy of big data in biomedicine and  we emphasise the obstacles that lie ahead for future  research pathways aimed at strengthening data privacy in  biomedical investigations. Both of these topics are covered  in detail throughout this article. After the paper was first  published, it was highlighted in the publication Biomedical  Research.
Keywords: Data Privacy; Biomedical ResearcH; Data Security; Bioethics; Genome Analysis